The Influence of Reading Comprehension Achievement at the Eighth Grade Students of SMP Muhammadiyah 1 Rawa Bening By Using DRTA and KWL Strategies - Dwi Andriani (English Department - University of Sultan Ageng Tirtayasa, 2017)
There are three objectives of this study : (1) to find out whether or not there was a significant difference in reading comprehension achievement of the students between before and after they were taught using DRTA strategy, (2) to find out whether or not there was a significant difference in reading comprehension achievement of the students between before and after they were taught using KWL strategy, and (3) to find out whether or not there was a significant difference in reading comprehension achievement between the students who were taught using DRTA strategy and those KWL strategy. The 90 samples out of 120 students from the eighth grade students were chosen by means purposive sampling technique. It used quasi-experimental method. The data was analyzed using t-test. The result showed there was a significant difference in reading comprehension achievement between before and after taught using DRTA strategy, there was a significant difference in reading comprehension achievement between before and after taught using KWL strategy, and there was a significant difference in reading comprehension achievement between the students who were taught using DRTA strategy and KWL strategy. Key Words: DRTA Strategy; KWL Strategy; Reading Comprehension Achievement.